Why the fuss? Friedman (1968) after fifty years - David E. W. Laidler (The University of Western Ontario, Department of Economics, 2018)
Friedman's Presidential Address was about "The Role of Monetary Policy". Its famous discussion of inflation-unemployment inter-relationships was subservient to this broader topic. The program it promoted influenced monetary policy in the '70s and early '80s with mixed results, but enough of it survived to be a clearly visible influence on today's inflation-targeting regimes.
Keywords: B22; B 31; E31; E52; 330